Effective Instructional Strategies for Elementary School Mathematics: A PRISMA-Guided Systematic Literature Review - Pratiwi, Nike; Atmoko, Adi; Taufiq, Ahmad; Faizah, Siti; Alfaris, Renaldy (Papanda Publisher, 2025)
Persistent deficiencies in elementary school students’ mathematics achievement, as evidenced by international assessments including PISA 2022, underscore the urgent need for a comprehensive synthesis of effective instructional strategies. Despite a growing body of individual studies, no systematic integration of evidence across multiple approaches and contexts existed for the 2020–2024 period. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. A systematic search across Scopus, Web of Science, ScienceDirect, and Google Scholar identified 12,945 records; following two-stage screening against pre-specified inclusion and exclusion criteria, 40 peer-reviewed empirical studies were retained for thematic analysis. Three dominant instructional themes emerged: manipulative-based learning, problem-based learning (PBL), and collaborative learning. All three demonstrated consistent positive effects on students’ conceptual understanding, critical thinking, and mathematical communication. The effectiveness of each strategy was moderated by teacher pedagogical competence, resource availability, and sociocultural context. Findings align with constructivist and sociocultural learning theories and corroborate recent meta-analytic evidence. A pronounced geographic concentration of studies in developed nations constitutes a critical knowledge gap. No single strategy is universally sufficient; an ecologically situated, multi-strategy framework supported by sustained teacher professional development and equitable resource policy is essential for advancing elementary mathematics education globally.